Strong enrichment of atmospherically relevant organic ions at the aqueous interface: the role of ion pairing and cooperative effects. Issue 42 (19th October 2018) - Ekholm, Victor; Caleman, Carl; Bjärnhall Prytz, Nicklas; Walz, Marie-Madeleine; Werner, Josephina; Öhrwall, Gunnar; Rubensson, Jan-Erik; Björneholm, Olle
Abstract : Surface affinity, orientation and ion pairing are investigated in mixed and single solute systems of aqueous sodium hexanoate and hexylammonium chloride. Abstract : Surface affinity, orientation and ion pairing are investigated in mixed and single solute systems of aqueous sodium hexanoate and hexylammonium chloride. The surface sensitive X-ray photoelectron spectroscopy technique has been used to acquire the experimental results, while the computational data have been calculated using molecular dynamics simulations. By comparing the single solute solutions with the mixed one, we observe a non-linear surface enrichment and reorientation of the organic ions with their alkyl chains pointing out of the aqueous surface. We ascribe this effect to ion paring between the charged functional groups on the respective organic ion and hydrophobic expulsion of the alkyl chains from the surface in combination with van der Waals interactions between the alkyl chains. These cooperative effects lead to a substantial surface enrichment of organic ions, with consequences for aerosol surface properties.